Hydrogen‐Bond‐Mediated Aglycone Delivery (HAD): A Highly Stereoselective Synthesis of 1, 2‐cis α‐D‐Glucosides from Common Glycosyl Donors in the Presence of Bromine. Issue 17 (12th March 2015) - Yasomanee, Jagodige P.; Demchenko, Alexei V.
Abstract Described herein is the expansion of the picoloyl protecting‐group assisted H‐bond mediated aglycone delivery (HAD) method recently introduced by our laboratory. At first it was noticed that high α‐stereoselectivity is only obtained with S‐ethyl glycosyl donors and only in the presence of dimethyl(methylthio)sulfonium trifluoromethanesulfonate (DMTST), in high dilution, and low temperature. Combining the mechanistic studies of the HAD reaction and bromine‐promoted glycosylations allowed a very effective method to be devised that allows for highly stereoselective α‐glycosidation of practically all common leaving groups (S‐phenyl, S‐tolyl, S/O‐imidates) at regular concentrations and ambient temperature.